A tungsten oxide dihydrate electrochromic nanofilm and a constant current electrodeposition preparation method thereof

The porous dihydr -tungsten oxide film prepared by the Hengli Electric Statistics method solves the problem of poor stability of existing tungsten oxide film, realizes high stability and excellent electrical discoloration properties, and is suitable for industrial production.

CN116253525BActive Publication Date: 2025-01-24UNIV OF SHANGHAI FOR SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211485384.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-01-24
Estimated Expiration
2042-11-24

Smart Images

  • Figure CN116253525B_ABST
    Figure CN116253525B_ABST
Patent Text Reader

Abstract

The present invention relates to a tungsten oxide dihydrate electrochromic nanofilm and a constant current electrodeposition preparation method thereof. The raw materials of the film include a tungsten source and an oxidant. The film contains a porous structure stacked by nanoparticles with a diameter of 10-100 nm. The thickness of the film is 100 nm-1 µm, the maximum light modulation amplitude can reach 91%, and the coloring efficiency can reach 250 cm 2 ·C ‑1 The preparation method comprises the following steps: mixing a tungsten source and an oxidant to obtain a reaction precursor solution; using the reaction precursor solution as an electrochemical deposition solution, using a conductive substrate as a working electrode, and using a three-electrode system to perform constant current electrodeposition in an electrolytic cell; after the deposition is completed, taking out the conductive substrate, washing and drying, and obtaining a dihydrate tungsten oxide electrochromic nanofilm. Compared with the prior art, the present invention has the advantages of uniform morphology, adjustable thickness, loose porous structure, good stability, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of material technology and electrochemical technology, and in particular to a tungsten oxide dihydrate electrochromic nano film and a constant current electrodeposition preparation method thereof. Background Art

[0002] With the continuous development of today's industrial society, environmental issues, the rational use of clean energy (such as solar energy, etc.), and the research and development of energy-saving products are increasingly attracting the attention of governments and researchers around the world. With the development of society, the application of high-tech energy-saving and environmental protection technologies can not only improve the production efficiency of enterprises and bring more profits, but more importantly, it can save energy and prevent pollution. This means that energy conservation and environmental protection are no longer a simple investment, but have formed considerable environmental benefits. Building a resource-saving and environmentally friendly society is increasingly valued by people, and energy-saving and environmental protection technologies have become a hot topic of research. Among them, green and environmentally friendly electrochromic technology has begun to enter the public eye. Electrochromism refers to the continuous and reversible color change of electrochromic materials under the stimulation of electric fields, that is, changes in optical transmittance, absorptivity and reflectivity. Products developed based on electrochromic technology have been applied in various fields, such as anti-glare rearview mirrors, smart windows, optical displays, etc. Among them, electrochromic smart windows can automatically change the color of windows, and can adjust the indoor temperature by regulating solar radiation. Therefore, they have received more and more attention and are expected to achieve large-scale electrochromic products.

[0003] Electrochromic materials are one of the core components of electrochromic products. Among many electrochromic materials, tungsten oxide has become one of the most widely studied electrochromic materials due to its advantages such as large light modulation, fast response speed and good stability. There are two methods for preparing tungsten oxide thin films: physical method and chemical method. The physical method mainly includes electron beam evaporation, magnetron sputtering, etc. The chemical method mainly includes chemical vapor deposition, electrodeposition, sol-gel method, hydrothermal method, etc. At present, the industrial production of tungsten oxide thin films mainly uses high-cost physical methods, which is not conducive to the development and large-scale application of tungsten oxide thin films.

[0004] Among the methods for preparing tungsten oxide thin films, the electrodeposition method has the advantages of low cost, simple process, and large-area preparation, and is expected to replace the physical method for the industrial preparation of tungsten oxide thin films. With the development of optoelectronic materials and devices, thin films prepared by electrodeposition have attracted widespread attention because of their unique advantages. Patil et al. successfully synthesized amorphous granular WO by applying a DC voltage in the range of ±1 V on the working electrode (ITO conductive glass) by cyclic voltammetry at a scan rate of 50 mV s. 3 The obtained film has a light modulation amplitude of 88.5% at 555 nm and shows a 132.7 cm 2 ·C -1The coloring efficiency of 2 mol·L -1 In KCl solution, a two-electrode system was used to apply a voltage of 5 V for 2 min to the working electrode (FTO conductive glass) to activate the working electrode; then, a voltage of -0.75~0.4V was applied to the working electrode in the deposition solution for 25 cycles using the cyclic voltammetry mode to strengthen the interface and form nuclei; finally, a constant voltage of -0.7 V was applied to the working electrode for 10 min using constant voltage electrodeposition to successfully prepare WO on FTO conductive glass. 3 ·2H 2 O film and achieved a light modulation amplitude of 86.5% at 632 nm (Applied Surface Science, 2022, 258). Ahn et al. first applied a square wave voltage of -0.7 V for 0.2 s to the working electrode, then applied a square wave voltage of 0 V for 1.0 s, and controlled the number of cycles to control the film thickness, successfully preparing porous WO 3 The film achieved a light modulation amplitude of 80.1% at 700 nm, and after a cycle of 1000 s, the light modulation amplitude decreased by 5.5% (Journal of Industrial and Engineering Chemistry, 2021, 94, 264-271).

[0005] Although electrodeposition technology has been applied to the preparation of tungsten oxide thin films, there are still some problems with the thin films prepared by electrodeposition. For example: (1) Tungsten oxide thin films prepared by cyclic voltammetry and constant voltage method usually have a dense structure. Due to the expansion effect of ion extraction and insertion on the film, dense films usually have poor stability. (2) Although porous tungsten oxide thin films can be prepared by pulse voltage electrodeposition, and the stability has been improved, most of the films are amorphous or have low crystallinity, and the bonding force between the film and the substrate is weak, so the stability cannot be effectively improved. In addition, the deposition time of tungsten oxide thin films prepared by pulse electrodeposition is long. The conductive substrate is immersed in the deposition solution for a long time, and the film is corroded by the deposition solution, making it difficult to improve its stability. (3) Tungsten oxide thin films prepared by electrodeposition contain a lot of water, including physically adsorbed water and crystallization water. When annealing is used to improve the stability of the film, the evaporation of physically adsorbed water will cause the film to fall off. The loss of crystallization water may cause the lattice of tungsten oxide to collapse, destroying the structure of tungsten oxide nanocrystals. Summary of the invention

[0006] The purpose of the present invention is to overcome at least one of the defects of the above-mentioned prior art and to provide a tungsten oxide dihydrate electrochromic nanofilm with uniform morphology, adjustable thickness, loose porous structure and good stability and a constant current electrodeposition preparation method thereof.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] In order to solve these problems, the present invention prepares a porous structure of tungsten oxide dihydrate (WO) by directly applying a constant current to the working electrode for electrodeposition. 3 ·2H 2 O) electrochromic film, and no annealing treatment is required. The obtained film has good crystallinity and the bonding strength between the film and the substrate is improved. The presence of crystal water enhances the WO 3 The method has low cost, simple operation, short deposition cycle, and can form a film in one time. 3 ·2H 2 The O film has high transparency, uniformity, and a strong bond between the film and the substrate, and has excellent electrochromic properties. By controlling the deposition time, the required thickness of the film can be easily controlled, which is suitable for industrial production. In the modern society that advocates energy conservation and environmental protection, this mild, simple process, and low-cost preparation method has a very broad application prospect. The specific scheme is as follows:

[0009] A tungsten oxide dihydrate electrochromic nano film, the raw materials of which include a tungsten source and an oxidant, and the film contains a porous structure stacked by nanoparticles with a diameter of 10-100 nm.

[0010] Furthermore, the film has a thickness of 100 nm-1 µm, a maximum light modulation amplitude of 91%, and a coloring efficiency of 250 cm 2 ·C -1 .

[0011] A constant current electrodeposition method for preparing the above-mentioned tungsten oxide dihydrate electrochromic nanofilm comprises the following steps:

[0012] A tungsten source and an oxidant are mixed to obtain a reaction precursor solution;

[0013] The reaction precursor solution is used as an electrochemical deposition solution, the conductive substrate is used as a working electrode, and a three-electrode system is used to perform constant current electrodeposition in an electrolytic cell;

[0014] After the deposition is completed, the conductive substrate is taken out, and after cleaning and drying, a tungsten oxide dihydrate electrochromic nano film is obtained.

[0015] Furthermore, the molar ratio of the tungsten source to the oxidant is 1:2 to 2:1.

[0016] Furthermore, before electrodeposition, the pH of the reaction precursor solution is adjusted to 1-5.

[0017] Furthermore, during electrodeposition, the current density was -0.5~-3.0 mA·cm -2 The deposition process of tungsten oxide is a reduction reaction, so the present invention needs to be carried out under a negative current density.

[0018] Furthermore, the electrodeposition time is 1-15 min.

[0019] Furthermore, the tungsten source includes Na 2 WO 4 ·2H 2 O, the oxidant includes H 2 O 2 Solution.

[0020] Furthermore, the conductive substrate includes ITO conductive glass.

[0021] Furthermore, nitric acid was used for pH adjustment.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) The present invention can conveniently adjust the thickness of the film by controlling the deposition time;

[0024] (2) In the present invention, the film presents a porous structure and has a larger specific surface area. Through the test of its electrochromic performance, the film has a larger optical modulation, a faster response speed, a higher coloring efficiency, and better stability;

[0025] (3) The preparation method of the present invention has low cost, simple process, and easy-to-obtain raw materials. It has low requirements for the experimental environment, does not produce toxic and harmful volatile gases, and is harmless to the human body;

[0026] (4) In the present invention, the film thickness can be adjusted between 100 nm and 1 µm according to demand, and has a porous structure composed of nanoparticles with a diameter of 10-100 nm. The maximum light modulation amplitude can reach 91%, and the coloring efficiency can reach 250 cm 2 ·C -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the WO prepared in Example 1 3 ·2H 2 SEM images of O films;

[0028] Figure 2 is the WO prepared in Example 1 3 ·2H 2 Grazing incidence X-ray diffraction (GIXRD) spectrum of O film (the incident angle is 0.1°, and the diffraction peak of the conductive substrate has been subtracted);

[0029] Figure 3 is the WO prepared in Example 1 3 ·2H 2 Thermogravimetric curve of O film;

[0030] Figure 4 is the WO prepared in Example 1 3 ·2H 2 Cyclic voltammetry curves of O thin films;

[0031] Figure 5 is the WO prepared in Example 1 3 ·2H 2 Photo of the color change of O film;

[0032] Figure 6 is the WO prepared in Example 1 3 ·2H 2 Transmittance curve of O film;

[0033] Figure 7 is the WO prepared in Example 1 3 ·2H 2 Response time curve of O film. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0035] A tungsten oxide dihydrate electrochromic nanofilm and a constant current electrodeposition preparation method thereof are as follows:

[0036] ① Mix sodium tungstate dihydrate, nitric acid, and hydrogen peroxide to obtain a reaction precursor solution. 2 O 2 The molar ratio of nitric acid to nitric acid is 1: 2 to 2: 1. Nitric acid is added to adjust the pH of the precursor solution to 1-5.

[0037] ② The reaction precursor solution obtained in step ① is used as an electrochemical deposition solution, and ITO conductive glass is used as a working electrode. A three-electrode system is used for cathode reduction constant current electrodeposition. The deposition time is set according to the film thickness requirement. After the deposition is completed, the conductive glass is taken out, rinsed with deionized water, and dried at room temperature and air atmosphere to obtain WO 3 ·2H 2 O film. The constant current density applied to the working electrode was -0.5~-3.0 mA·cm -2 The deposition time is set according to the film thickness requirement and is 1-15 min.

[0038] The present invention is described in detail below in conjunction with the examples, but the following examples are not intended to limit the present invention, and the raw materials in the following examples are basically commercially available products. The counter electrode used does not react with the deposition liquid, and the area can be adjusted according to the volume of the electrolytic cell; the selection of the reference electrode must be suitable for the composition of the deposition liquid; the counter electrode can use other types of conductive substrates as needed, and its size can be adjusted according to the volume of the electrolytic cell. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention are deemed to be equivalent replacement methods and are included in the protection scope of the present invention.

[0039] Example 1

[0040] A tungsten oxide dihydrate electrochromic nanofilm and a constant current electrodeposition preparation method thereof are as follows:

[0041] (1) Put 1.65 g Na 2 WO 4 ·2H 2 O dissolved in 0.03 mol·L -1 H 2 O 2 Add appropriate amount of HNO 3 The pH value of the sediment solution was adjusted to 1 and stirred for 30 min to obtain WO 3 Sedimentation fluid.

[0042] (2) 2.5 × 5 cm 2 The ITO conductive glass was washed with deionized water and ethanol in turn, and electrochemical deposition was performed using a three-electrode system. 2 Platinum sheets were used as working and counter electrodes, and Ag / AgCl electrode was used as reference electrode. -1.0 mA·cm -2 The constant current density was maintained for 5 min.

[0043] (3) Take out the deposited conductive glass, rinse it with deionized water, and dry it at room temperature and air atmosphere to obtain WO with the performance to be tested. 3 ·2H 2 O film.

[0044] The WO prepared in this example 3 ·2H 2 SEM images of O films are shown in Figure 1 As shown in FIG. 1 , the film has a porous structure composed of nanoparticles with a size of 10-100 nm. 3 ·2H 2 The grazing incidence X-ray diffraction spectrum of O film is shown in Figure 2 As shown in FIG. 1 , the sharp diffraction peak of the film is basically consistent with the standard card (JCPDS card No. 18-1420). 3 ·2H 2 Thermogravimetric analysis curve of O film is shown in Figure 3 As shown, the three mass loss processes in the figure correspond to the loss of physically adsorbed water and the continuous loss of two crystal waters.

[0045] The electrochromic performance test of the film obtained in this example was carried out in a three-electrode system, using an Ag / AgCl electrode as a reference electrode and a 1 mol·L -1 H 2 SO 4 The cyclic voltammetry (CV) test was performed at a voltage of -0.6 to 0.6 V with a scan rate of 0.1 V·s -1 The transmittance was tested in the wavelength range of 300-1100 nm by using an electrochemical workstation in conjunction with a UV-visible-near infrared spectrophotometer. The light modulation amplitude is the difference between the transmittance in the bleached state and the transmittance in the colored state. At a wavelength of 622 nm, the light modulation amplitude reaches a maximum. A square wave potential of -0.6 V and 0.3 V was applied for 35 s and 25 s, respectively, to the WO prepared in this example. 3 ·2H 2 O film was tested for response time, and all data were measured at 622 nm.

[0046] The WO prepared in this example 3 ·2H 2 All transmittances of O films are tested with air as the baseline, that is, the transmittance of air is 100%. Figure 5 WO prepared in this example 3 ·2H 2 Color change photos of O film at voltages of -0.6 V and 0.3 V. Figure 6 WO prepared in this example3 ·2H 2 The transmittance curve of the O film shows that at 622 nm, the transmittances of the faded and colored states are 94.1% and 3.1%, respectively, with a maximum light modulation amplitude of 91.0%. Figure 7 WO prepared in this example 3 ·2H 2 The response time curve of the O film is calculated to show that when the light modulation amplitude changes by 90%, the WO 3 ·2H 2 The coloring time of the O electrochromic device is about 8.6 s, and the fading time is about 13.3 s.

[0047] Example 2

[0048] A tungsten oxide dihydrate electrochromic nanofilm and a constant current electrodeposition preparation method thereof are as follows:

[0049] (1) Put 1.65 g Na 2 WO 4 ·2H 2 O dissolved in 0.03 mol·L -1 H 2 O 2 Add appropriate amount of HNO 3 The pH value of the sediment solution was adjusted to 3 and stirred for 30 min to obtain WO 3 Sedimentation fluid.

[0050] (2) 2.5 × 5 cm 2 The ITO conductive glass was washed with deionized water and ethanol in turn, and electrochemical deposition was performed using a three-electrode system. 2 Platinum sheets were used as working and counter electrodes, and Ag / AgCl electrode was used as reference electrode. -0.5 mA·cm was applied to the working electrode. -2 The constant current density was maintained for 15 min.

[0051] (3) Take out the deposited conductive glass, rinse it with deionized water, and dry it at room temperature and air atmosphere to obtain WO with the performance to be tested. 3 ·2H 2 O film.

[0052] Example 3

[0053] A tungsten oxide dihydrate electrochromic nanofilm and a constant current electrodeposition preparation method thereof are as follows:

[0054] (1) Put 1.65 g Na 2 WO 4 ·2H2 O dissolved in 0.05 mol·L -1 H 2 O 2 Add appropriate amount of HNO 3 The pH value of the sediment solution was adjusted to 5 and stirred for 30 min to obtain WO 3 Sedimentation fluid.

[0055] (2) 2.5 × 5 cm 2 The ITO conductive glass was washed with deionized water and ethanol in turn, and electrochemical deposition was performed using a three-electrode system. 2 Platinum sheets were used as working and counter electrodes, and Ag / AgCl electrode was used as reference electrode. -3.0 mA·cm was applied to the working electrode. -2 The constant current density lasted for 1 min.

[0056] (3) Take out the deposited conductive glass, rinse it with deionized water, and dry it at room temperature and air atmosphere to obtain WO with the performance to be tested. 3 ·2H 2 O film.

[0057] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A constant current electrodeposition method for preparing a tungsten oxide dihydrate electrochromic nanofilm, characterized in that: The method comprises the following steps: A tungsten source and an oxidant are mixed to obtain a reaction precursor solution; The reaction precursor solution is used as an electrochemical deposition solution, the conductive substrate is used as a working electrode, and a three-electrode system is used to perform constant current electrodeposition in an electrolytic cell; After the deposition is completed, the conductive substrate is taken out, washed and dried to obtain a tungsten oxide dihydrate electrochromic nanofilm, which contains a porous structure composed of nanoparticles with a diameter of 10-100 nm. Wherein, the molar ratio of the tungsten source to the oxidant is 1: 2 to 2: 1; Before electrodeposition, the pH of the reaction precursor solution was adjusted to 1-5; During electrodeposition, the current density is -0.5~-3.0 mA·cm -2 ; The tungsten source includes Na2WO4·2H2O, and the oxidant includes H2O2 solution.

2. The constant current electrodeposition preparation method of a tungsten oxide dihydrate electrochromic nanofilm according to claim 1, characterized in that: The film has a thickness of 100 nm-1 µm, a maximum light modulation amplitude of 91%, and a coloring efficiency of 250 cm 2 ·C -1 .

3. The constant current electrodeposition preparation method of a tungsten oxide dihydrate electrochromic nanofilm according to claim 1, characterized in that: The electrodeposition time is 1-15 min.

4. The method for preparing a tungsten oxide dihydrate electrochromic nanofilm by constant current electrodeposition according to claim 1, characterized in that: The conductive substrate comprises ITO conductive glass.

5. The method for preparing a tungsten oxide dihydrate electrochromic nanofilm by constant current electrodeposition according to claim 1, characterized in that: Nitric acid was used for pH adjustment.